Investigating Cortical Reorganization Following Motor Cortex Photothrombotic Stroke in Mice - Eckert, Zachary (Université d'Ottawa / University of Ottawa, 2024)
Following a stroke, normal usage of the impaired limb guides spontaneous recovery across many months or even years; however, recovery is rarely complete. Pre-clinical tools are needed to investigate stroke-induced cortical reorganization over long periods. This thesis aims to characterize stroke impairment and spontaneous recovery in parallel with a battery of behaviour tasks in a mouse model of focal stroke. Young adult Thy1-ChR2 mice were implanted with a transcranial window over the intact skull permitting cortex visualization and enabling longitudinal assessments with light-based motor mapping and intrinsic signal optical imaging. Furthermore, mice were tested on sensorimotor behavioural tasks in parallel to the mapping experiments. These experiments allowed for the quantification of impairments in the sensorimotor cortex and forelimb function while identifying regions within the sensorimotor cortex that show re-mapping associated with behavioural recovery. Following primary motor cortex-stroke induction, both sensory and motor map impairments occurred. Sensory map transient impairments recovered within the same atlas-defined regions two weeks after a primary motor cortex stroke as identified by intrinsic signal optical imaging. In contrast, motor forelimb recovery was observed four weeks after the stroke in the peri-infarct region, the supplemental motor cortex, and the contralesional motor cortex. This recovery was identified through a combination of analyses, including changes in the mapped area and the amplitude of evoked forelimb movements using light-based motor mapping. Behavioural recovery occurred four to six weeks post-stroke, depending on the sensitivity of the task in forelimb impairment. Additionally, the contralesional hemisphere and forelimb did not show impairment acutely but evoked forelimb amplitude was significantly increased by post-stroke week four for both forelimbs. As the first study to conduct within-animal longitudinal spontaneous recovery sensory and motor map experiments using bilateral forelimb and hemispheric representations, we show that 1) photothrombotic stroke impacts both forelimb representations pertained within the ipsilesional hemisphere in LBMM experiments, 2) recovery of the impaired forelimb occurs ipsilesionally and contralesionally and, 3) impairments from stroke observed through motor mapping are functionally relevant and precede behavioural recovery ranging from zero to two or more weeks depending on the motor cortex's involvement in the behavioural task.
Keywords: Stroke; Spontaneous Recovery; Non-invasive Stimulation; Optogenetics; Rodent Model; Light-Based Motor Mapping; Motor Mapping; Intrinsic Signal Optical Imaging; Sensory Mapping; String-Pull Task; Grid Walking Task; Cylinder Task; Post-Stroke Recovery; Motor Cortex; Sensory Cortex; Neural Reorganization